Methods Of Management And Control Of General Production Costs (Eurasian Scientific Herald, 2026)
In the article The purpose of this article is to study the issues of conducting audits in order to properly maintain and effectively use the accounting records of production costs and general production costs of products (works and services) in business entities and make specific decisions on minimizing costs, as well as to provide feedback on improving the theoretical and practical foundations of accounting and auditing based on the requirements of a market economy.